Trajectories for Engaging Rural Communities in Non-Governmental Organization Programmes for Sustainable Community Development in Rivers State - Adaba Williams (East Asian Journal of Multidisciplinary Research, 2022)
The study investigated “trajectories for engaging rural communities in non-governmental organization programmes for sustainable community development in Rivers state” Three objectives, three research questions and hypotheses were tested in the study. The design used for the study was a descriptive survey. The population of the study was all rural community leaders and non-governmental organizations officers in Rivers State. Statistics showed that there were 1,170 community leaders in Rivers state. The sample size of the study was 342 community leaders and 89 non-governmental organization officers. The instrument used in the study was a close ended questionnaire titled “Trajectories for Engaging Rural Communities in Non-Governmental Organization Programmes for Sustainable Community Development”. The instrument was validated and tested for reliability using Kuda-Richardson 21, whereby 0.83 reliability coefficient was obtained. Mean and Standard Deviation was used as statistical tool for data analysis and z-test was used to test hypotheses at 0.05 level of significance.